Pengaruh Citra Merek, Kualitas Produk Dan Harga Terhadap Keputusan Pembelian Hijab Rabbani (Studi Pada Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Islam Malang) - Dina Alfina Helmania Putri; Achmad Agus Priyono; Restu Millaningtyas (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This research aims to determine and analyze brand image, product quality and price which simultaneously have a significant influence on the decision to purchase the Rabbani hijab among students from the Faculty of Economics and Business at the Islamic University of Malang. This population was taken because students play an important role in the daily use of the hijab, with the consideration that this population can be reached by researchers. This population was taken because students play an important role in the daily use of the hijab, with the consideration that this population can be reached by researchers. The sample was determined using the Malhotra formula where 20x5 and 100 respondents were found. The research results show that the variables brand image, product quality and price have a significant influence simultaneously on purchasing decisions. Brand image variables partially influence purchasing decisions. Product quality variables partially influence purchasing decisions. The price variable partially influences purchasing decisions the Rabbani hijab among students at the Faculty of Economics and Business at the Islamic University of Malang and have a contribution to the purchasing decision of 93% , while the remaining 7% is explained by other variables outside the variables in this study. Keywords: Brand Image, Product Quality, Price, And Purchasing Decisions